Práticas sociais e espaço urbano: diferentes cartografias e representações sobre o Bairro Frei Damião - Feitosa, Antonio Lucas Cordeiro (2014)
This work takes as field Frei Damião district, in Juazeiro do Norte city, Ceará, to reflect on the images of outskirts that has been built about this place, the social practices of its inhabitants and its urban space. The area of Frei Damião neighborhood is defined by the municipality as a wide area that makes boundary with others counties. However, residents and other inhabitants of the city restrict the neighborhood to a region of rectangular geometric shape, densely populated. Taking this last representation of the territory as research locus, it was realized that this region is divided into three different areas, either by neighborhood residents and other inhabitants of Juazeiro do Norte. These areas, called by us as “territorialities” are: “Vila Real”, “Frei Damião” and “Baixa da Raposa”. In addition to this segmentation, the social networks of relationships around the four religious chapels that are in the neighborhood and the soccer games played by young male men in improvised fields, the "rachas", operate new cartographies of the space. To understand these areas is necessary to know the specific characteristics of each one, the relations between them, the understanding of the neighborhood as a whole and the relations between the district and the city. These territorialities are marked by symbolic boundaries and socio-spatial hierarchical stratifications constituted by: images and self-images, nomination systems, historical origins, the regulation of social life intensity, distribution of public and private facilities and patterns. These territorial and social dynamics lead us to question the very notion of district and think about the friction between different mappings and social practices of the residents. of housing. In addition, the historical origin of the district Frei Damiao also helps us clarify this urban dynamics and its presentations in the city and by the city, assigning the district as a “slum” or periphery. The structuring of the neighborhood, after the urban settlement that originated it, was planned keeping in view his arrest as peripherals / slum. It turns out forms of trading of its representation and its implications on the local urban space.